Decoding the Impact of Drought Stress Induced Redox-Metabolic Shift in Flag Leaf During Grain-Filling Stage on Kernel Aroma Quality and Productivity in Some Indigenous Aromatic Rice Cultivars of West Bengal, India - Dey, Nivedita; Bhattacharyya, Trisha; Bhattacharjee, Soumen (Journal of plant growth regulation, 2023)
Yield and aroma stability under drought in indigenous aromatic rice cultivars (IARCs), which needs significant attenuation of reduction of grain yield and quality through redox metabolic reprograming in contributory flag leaf was rarely studied and hence was the subject of present investigation. The redox landscaping of flag leaves of experimental IARCs done ( Oryza sativa L., Cultivars Tulaipanji, Badshabhog, Jamainadu, and Sitabhog) during ensuing drought stress at grain-filling stage (65% of field capacity) and stress withdrawal (after 6 days) revealed tilt in the magnitude of redox homeostasis (assessed in terms of oxidation of DCFDA, accumulation of O 2 ⋅− , H 2 O 2, free radical scavenging property, non-protein thiol compounds, redox osmolytes, antioxidant pigments, and ROS-antioxidant interaction index), efficacy of RboH- ascorbate–glutathione/catalase pathway and sensitive biomarkers oxidative stress (accumulation of free carbonyl compounds, hydroperoxide, conjugated diene, and thiobarbituric acid reactive substances). The Cultivars capable of regulating ROS-antioxidant interaction dynamics at metabolic interface in flag leaf (Badshabhog and Tulaipanji) and able to prevent oxidative deterioration of flag leaf caused better restoration of aroma profile, 2-acetyl-1-pyrroline (2AP) content, agronomic characters, seed yield, and kernel quality than the others (Jamainadu and Sitabhog). Further, germplasm specific comparative assessment of metabolites shared by redox osmolyte proline and (2AP), exhibited metabolic cross talking toward regulation of dehydration induced oxidative stress and restoration of aroma production. Ability of maintenance of aromatic compounds, agronomic characters, seed yield, and kernel quality under drought stress through redox-regulatory acclimatory events of flag leaves in IARCs is suggested.